2022
DOI: 10.3389/fmed.2022.838975
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Matrix Interactions Contribute to Barrier Function in Human Colon Organoids

Abstract: The importance of cell-matrix adhesion to barrier control in the colon is unclear. The goals of the present study were to: (i) determine if disruption of colon epithelial cell interactions with the extracellular matrix alters permeability control measurement and (ii) determine if increasing the elaboration of protein components of cell-matrix adhesion complexes can mitigate the effects of cell-matrix disruption. Human colon organoids were interrogated for transepithelial electrical resistance (TEER) under cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…6,7 Our data showed that Ginkgetin was found had a protective effect on intestinal barrier function in DSS-induced enteritis mice and TNFαinduced organoid models, further confirming that the regulation of intestinal barrier function is one of the targets for protecting against colitis. Where TEER is used as an indicator of barrier integrity, our data show that colon tissue and monolayers of colonic organoids have robust TEER development, which is consistent with the report by Jelinsky et al and Varani et al [28][29][30] However, there was severe loss of TEER after stimulation with DSS and TNF-α, which was restored by GK treatment. monolayer of columnar intestinal epithelial cells structural basis for maintaining the integrity of the intestinal barrier.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6,7 Our data showed that Ginkgetin was found had a protective effect on intestinal barrier function in DSS-induced enteritis mice and TNFαinduced organoid models, further confirming that the regulation of intestinal barrier function is one of the targets for protecting against colitis. Where TEER is used as an indicator of barrier integrity, our data show that colon tissue and monolayers of colonic organoids have robust TEER development, which is consistent with the report by Jelinsky et al and Varani et al [28][29][30] However, there was severe loss of TEER after stimulation with DSS and TNF-α, which was restored by GK treatment. monolayer of columnar intestinal epithelial cells structural basis for maintaining the integrity of the intestinal barrier.…”
Section: Discussionsupporting
confidence: 91%
“…Briefly, colon organoids were dissociated into single cells and seeded into the Matrigel‐coated Transwell upper chamber at a density of 2 million cells/mL. The cells were incubate at 37°C and 5% CO 2 for 1 day, and after TNF‐α and GK intervention, the TEER value of monolayer cells was measured using a resistive system 29,30 …”
Section: Methodsmentioning
confidence: 99%
“…Using human colonoids/colonoid monolayers and cell line cultures, its capacity to promote mucosal healing and intestinal barrier restoration was evaluated by analyzing the gene expression of key barrier proteins and TEER [58]. In a series of related studies, the multimineral extract, Aquamin, derived from red marine algae, was shown to improve barrier function in both control and UC colonoids compared with untreated controls [54][55][56]. When human UC colonoids were treated with Aquamin morphometric analysis showed modestly increased lumen diameter and wall thickness, and proteomic analysis showed increased barrier function markers, ion transporters, and mucin, compared with controls, suggesting a potential benefit for increased mineral consumption in UC [55].…”
Section: Barrier Functionmentioning
confidence: 99%
“…The implications of a compromised barrier in vivo include increased paracellular diffusion, and potential exposure of immune cells to luminal content, including microbiota, initiating a perpetuating inflammatory response [14]. Our understanding of factors affecting barrier function has advanced considerably with the use of organoids [13,54].…”
Section: Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation